TANTANGAN DAN STRATEGI MENGELOLA KELAS DALAM MICRO TEACHING : SEBUAH ANALISIS - Ginting, Rahmadani Fitri; Syahir, Muhamad (Cahaya Ilmu Bangsa Institute, 2024)
This research aims to analyze the challenges faced in classroom management during micro teaching activities and the strategies that can be applied to overcome these challenges. The method used in this research is library research, by collecting and analyzing information from various literary sources, including books, scientific journals and related articles. The research results show that the main challenges in classroom management during micro-teaching include managing student behavior, time management, and creating a conducive learning environment. To overcome these challenges, the recommended strategies include implementing effective classroom management techniques, using varied learning media, and developing good communication skills. This research is expected to provide useful insights for prospective teachers in improving their classroom management skills during the teaching and learning process.